HUBUNGAN ANTARA EFIKASI DIRI DENGAN SIKAP ORANG TUA MENGENAI PERTOLONGAN PERTAMA TERSEDAK PADA ANAK USIA DINI - Silvilia, Gusti Ayu Made Novianti; Juniartha, I Gusti Ngurah; Devi, Ni Luh Putu Shinta; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023, 2024)
Early childhood carries risks in emergency situations, one of which is choking. Young children are susceptible to choking incidents due to their cognitive and motor development, particularly the oral phase. A good self-efficacy is necessary for effective first aid during choking incidents and can influence the attitudes and behaviors of parents. This study aims to analyze the relationship between self-efficacy and parental attitudes regarding first aid for choking incidents in young children in the South Denpasar IV Primary Health Center area. The method used is quantitative research with a descriptive correlational design. The sampling technique employed is cluster random sampling, with a sample size of 81 parents (mothers/fathers) who have young children (0-5 years old) in the South Denpasar IV Primary Health Center area. Data collection was done using offline questionnaires. The Spearman Rank test yielded a p-value of 0.000 (?=0.05) and an r-value of 0.456, indicating a significant correlation with a moderately strong correlation strength and a positive relationship between self-efficacy and parental attitudes regarding first aid for choking incidents in young children in the South Denpasar IV Primary Health Center area. The positive relationship indicates that higher levels of self-efficacy are associated with higher levels of parental attitudes towards first aid for choking incidents in young children, and vice versa. The researchers recommend that the South Denpasar IV Primary Health Center and nurses organize activities such as training in first aid for choking incidents in young children to enhance and maintain good and positive self-efficacy and parental attitudes.